Cognitive Outcomes Following Arterial Ischemic Stroke in Infants and Children. (July 2014) - Hajek, Christine A.; Yeates, Keith Owen; Anderson, Vicki; Mackay, Mark; Greenham, Mardee; Gomes, Alison; Lo, Warren
This study sought to investigate cognitive outcomes following pediatric arterial ischemic stroke and explore predictors. Participants included 36 children with perinatal or childhood arterial ischemic stroke and a comparison group of 15 children with asthma. Outcomes included cognitive ability, executive functions, and neurological function (Pediatric Stroke Outcome Measure). Magnetic resonance imaging measured lesion location and volume. Mean cognitive scores were at the low end of the average range. Children with arterial ischemic stroke performed significantly below normative populations and significantly below the asthma group on inhibitory control (Cohen's d = .68). Both the Pediatric Stroke Outcome Measure and lesion volume were negatively correlated with cognitive outcome (Spearman r = –.01 to –.42 Pediatric Stroke Outcome Measure; r = –.14 to –.32 Volume). Following arterial ischemic stroke, children performed at the low end of the average range on measures of cognitive functioning. Cognitive outcomes depend on a variety of factors.